P2-3-8. Change of cross frequency coupling by symptom provocation in Obsessive Compulsive Disorder (OCD) based on sLORETA. Issue 5 (May 2018) - Yoshimura, Masafumi; Pascual-Marqui, Roberto; Nishida, Keiichiro; Kitaura, Yuichi; Mii, Hiroshi; Saito, Yukiko; Ikeda, Shunichiro; Katsura, Koji; Ueda, Satsuki; Minami, Shota; Isotani, Toshiaki; Kinoshita, Toshihiko
Abstract : We investigated the changes in directional cross frequency interactions between theta and alpha oscillations, across six cortical regions, induced by a symptom provocation procedure, in patients with OCD, and in normal controls. Nine OCD outpatients and nine controls participated in this study. Eyes closed EEG was recorded before and under the instruction to imagine that the towel placed on their hands is contaminated (symptom provocation, SP). Cortical electric neuronal activity were calculated with sLORETA at medial-prefrontal, precuneus, inferior-parietal, and dorsolateral-prefrontal cortices. Instantaneous amplitudes for the theta and alpha bands were obtained and used for computing Granger causal directional cross-frequency, cross-cortical interactions. In controls, SP is characterized by a significant increase in mPFC theta due to right fronto-parietal alpha. In contrast, SP in the OCD group mainly displayed alpha-alpha RIPL alpha decrease due to RDLPFC. A direct comparison of OCD and normal controls showed significant frontal decreases of theta-alpha interactions before SP. The symptom provocation procedure induced functional changes of cross-frequency connections in both groups involving core right hemisphere network nodes. Functional cross-frequency interactions involving all frontal nodes were decreased in OCD compared to controls during SP. These results support the use of cross-frequency interactions a possible trait marker of OCD.